2018
DOI: 10.1016/j.ridd.2018.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Parental views on special educational needs provision: Cross-syndrome comparisons in Williams Syndrome, Down Syndrome, and Autism Spectrum Disorders

Abstract: In contrast to previous studies, educational provision and satisfaction with educational provision are syndrome-specific. These results also highlight the need for training and raising awareness about the specific needs of children with neurodevelopmental disorders. In addition, our findings suggest improved communication between parents and the school is required about the type of support children with SEND are receiving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 19 publications
(35 reference statements)
2
22
0
Order By: Relevance
“…Our dichotomous variable may have missed other nuances in the influence of diagnosis on satisfaction, however. For example, van Herwegen, Ashworth & Polikara (2018) found that children with Down syndrome in the UK were more likely to access 1:1 support than parents of children with other aetiologies. Other limitations of the study include the use of parent report survey data, that is always prone to shared method variance.…”
Section: Discussionmentioning
confidence: 99%
“…Our dichotomous variable may have missed other nuances in the influence of diagnosis on satisfaction, however. For example, van Herwegen, Ashworth & Polikara (2018) found that children with Down syndrome in the UK were more likely to access 1:1 support than parents of children with other aetiologies. Other limitations of the study include the use of parent report survey data, that is always prone to shared method variance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many mainstream schools often have support staff with special education needs (SEN) training for children with ASD. In contrast, there are no specialist schools for children with WS and even SEN staff and schools have little understanding of WS (Van Herwegen, Ashworth, & Palikara, ). However, it is possible that parents of children with ASD find choosing the right school (specialist or mainstream) or specific aspects of education provision particular stressful (see McNerney, Hill, & Pellicano, for a discussion).…”
Section: Discussionmentioning
confidence: 99%
“…; van Herwegen et al . ). Research on neuroplasticity emphasises how learning experiences during early sensitive periods have a critical impact on neurocognitive development (Johnson & Munakata ).…”
Section: Adaptive Profile In Autism Spectrum Disordermentioning
confidence: 97%
“…Such knowledge, in turn, is critical to inform the use of early intervention targets and strategies to address shared and distinctive needs across neurodevelopment disorders. This is particularly important in the case of WS, as tailored, empirically supported early interventions to enhance adaptive outcomes in this population are largely lacking van Herwegen et al 2018). learning experiences during early sensitive periods have a critical impact on neurocognitive development (Johnson & Munakata 2005).…”
Section: Current Studymentioning
confidence: 99%